Work-Life Balance Perawat Wanita di RSUP Padang - Fitria Rahmi (Strategic: Journal of Management Sciences, 2022)
Objective. The purpose of this research is to obtain an overview of the work-life balance among the female nurses at the Inpatient Installation of Non-Surgical Internal Medicine at the Central General Hospital of DR. M. Djamil Padang. Respondents and the types of sampling techniques were using the saturated sampling, as many as 74 female nurses. The data were obtained through a measuring instrument, namely the Work-Life Balance Scale from Fisher, Bulger, and Smith (2009) which has been modified by Novelia (2013). Research Method. The method used in this research is the descriptive quantitative. Results. Based on the results of the research, it was found that the majority of female nurses has a high level of the work-life balance. Conclusion. This means that female nurses have been able to work to develop the role that they live by being able to manage the time between work and personal life with their good ability to regulate personal life so as not to interfere with the work they do.